Brexit: surname diversity and voting patterns. Issue 4 (1st August 2016) - Borja, Mario Cortina; Stander, Julian; Valle, Luciana Dalla
Abstract : Mario Cortina Borja, Julian Stander and Luciana Dalla Valle examine associations between the results of the EU referendum and surname diversity Abstract : Mario Cortina Borja, Julian Stander andLuciana Dalla Valle examine associations between the results of the EU referendum and the prevalence of unique surnames across the UK